ANALISIS PERAN GURU DALAM PEMBELAJARAN MEMBACA PUISI SISWA DENGAN METODE DEMONSTRASI KELAS V SDN 2 BALEWANGI - Hermawan, Asep; Indriati Widyaningsih, Yennie (Bale Aksara, 2021)
The purpose of this study was to identify and identify the difficulties of learning to read poetry, the role of the teacher and the obstacles of the teacher in learning to read poetry using the demonstration method for the fifth grade students of SDN 2 Balewangi. The method used in this research is descriptive qualitative using data collection techniques in the form of observation, interviews, and documentation. Check the validity of the data using triangulation. The results showed that (1) The teacher's role in learning to read poetry has been seen very well, proven by the seriousness of the teacher. The teacher not only teaches classically, but the teacher has played its role as a facilitator by facilitating students both inside and outside the classroom. (2) Teachers' obstacles in learning to read poetry are caused by student factors and teacher factors